PERANCANGAN DAN ANALISA PERBANDINGAN ANTARA DELAY DAN THROUGHPUT PADA VIDEO STREAMING MENGGUNAKAN IPv4 DAN IPv6 TUNNELING - Sajati, Haruno; Nugrahenny, Dwi; Nugroho, Eko Cahyo (Sekolah Tinggi Teknologi Adisutjipto, 2013)
Along with the rapid growth of the Internet, causing problem in the allocation of IPv4 addressing. Therefore, IPv4 only have less than 4 billion addresses and will soon be exhausted. Therefore, IPv6 has been created and used hexadecimal system on it addressing and has very large address allocation that is 3,4 x 1038 addresses. But now many network infrastructures in terms of hardware and software that have not fully support IPv6. So, the devices that still using IPv4 can through IPv6-based network infrastructures, they can use tunneling technique. This makes the emergence of the idea to test the delay and throughput in streaming video system which has a heavy workload on the network. Video streaming system on Vision 1.0 application takes advantage motor stepper webcam in order to support the visibility of the image that can be captured. Then the client who connected to the server can control remotely the motor stepper webcam. On the implementation phase, Vision 1.0 is running on IPv4 and IPv6 network. Next on the testing phase, carried out delay and throughput data collections from those both network systems. From the obtained results in testing, showed no significant difference. So, in general, the performance difference is not too pronounced when the video streaming system is running on both network systems. However, from a comparison based on mean value of delay and throughput, IPv4 is still superior due to the header of the data packet does not as big asIPv6 header which of course affects the packet data frame size, then the traffic network more crowded.